2013
DOI: 10.3390/ph6050579
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Mammalian Cell Line Development Technologies for Recombinant Protein Production

Abstract: From 2006 to 2011, an average of 15 novel recombinant protein therapeutics have been approved by US Food and Drug Administration (FDA) annually. In addition, the expiration of blockbuster biologics has also spurred the emergence of biosimilars. The increasing numbers of innovator biologic products and biosimilars have thus fuelled the demand of production cell lines with high productivity. Currently, mammalian cell line development technologies used by most biopharmaceutical companies are based on either the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
210
0
19

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 281 publications
(229 citation statements)
references
References 132 publications
(160 reference statements)
0
210
0
19
Order By: Relevance
“…The authors demonstrated that Raman spectroscopy is capable to discriminate producing and nonproducing CHO cells based on their biochemical fingerprints, which were detected from living single cells without the use of external labels. Classical methods for the identification and selection of recombinant mammalian high-producer cell lines are laborious and time-consuming, and often focus on invasive upstream process analyses [6,7]. After cell transfection with the expression vector and cell growth under selection pressure, state-of-the-art methods require minimal dilution cloning procedures on the heterogeneous cell pool to allow the formation of single clonal cell colonies [7].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The authors demonstrated that Raman spectroscopy is capable to discriminate producing and nonproducing CHO cells based on their biochemical fingerprints, which were detected from living single cells without the use of external labels. Classical methods for the identification and selection of recombinant mammalian high-producer cell lines are laborious and time-consuming, and often focus on invasive upstream process analyses [6,7]. After cell transfection with the expression vector and cell growth under selection pressure, state-of-the-art methods require minimal dilution cloning procedures on the heterogeneous cell pool to allow the formation of single clonal cell colonies [7].…”
mentioning
confidence: 99%
“…Classical methods for the identification and selection of recombinant mammalian high-producer cell lines are laborious and time-consuming, and often focus on invasive upstream process analyses [6,7]. After cell transfection with the expression vector and cell growth under selection pressure, state-of-the-art methods require minimal dilution cloning procedures on the heterogeneous cell pool to allow the formation of single clonal cell colonies [7]. Then, in most cases, clonal cell colonies are picked manually, which are then transferred into a new culture vessel and expanded for several weeks, before subsequent analysis of protein titers can be performed.…”
mentioning
confidence: 99%
See 3 more Smart Citations